IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE GI (GROUP INVESTIGATION) UNTUK MENINGKATKAN HASIL DAN AKTIVITAS BELAJAR PKn PADA SISWA KELAS VII 2 SMP NEGERI 2 SINGARAJA TAHUN AJARAN 2012/2013 - NI PUTU NOVI SUARINI (Universitas Pendidikan Ganesha, 2013)
ABSTRACTThis research is aimed at a class action: (1) to improve learning outcomesCivics class VII 2 SMP Negeri 2 Singaraja, (2) to enhance learning activitiesCivics class VII 2 SMP Negeri 2 Singaraja, (3) to determine the constraintsconstraints experienced by students in the application of cooperative learningmodel type Group Investigation (GI). The research was conducted in two cycles,each cycle consisting of four phases are: planning, implementation, and evaluationphases of reflection phase. The subjects were students of class VII 2 SMP Negeri2 Singaraja, the number of students 42 people consisting of 22 male students and20 female students. Data analysis using quantitative descriptive method withqualitative meaning. The results in the first cycle, the average value of studentlearning outcomes is at 79.28 and categorized simply by the absorption of 79.28%and 78.57% for classical completeness, the results on the second cycle, theaverage value of student learning outcomes is equal to 90, and included in bothcategories with 90% absorption and 100% classical completeness. Activities ofstudents in the first cycle included in the category is quite active, whereas activityof students in the second cycle included in the category of very active. Some ofthe obstacles encountered in the implementation of cooperative learning model GItype, the first students are not familiar with cooperative learning model GI type,both students' ability to express their opinions is relatively less, and there are threegroups the ability to present and clarify the results of the discussion are lesssuccessful. Based on the above results, it is suggested to teachers who seekimprovement Civics outcomes and learning activities to apply the learning modelGI Cooperative Study on Civics learning as an alternative to improve learningoutcomes and learning activities Civics.Key Words: Group Investigation, Results and Learning Activities